404 Mesonephric adenocarcinoma; a case report and review of the literature. (13th November 2020) - Daas, M; Addley, S; Soleymani Majd, H; Jackson, E; Alazzam, M
Abstract : Introduction: Mesonephric cancer is an extremely rare form of neoplasms that arises from the mesonephric duct remnants, the majority of cancers originating from the mesonephric duct are in the cervix, only 67 cases were reported in the literature. We present here the case of a 53-year-old woman who previously had a subtotal hysterectomy and was referred to the colposcopy clinic due to borderline changes in her cervical smear, Punch biopsy reported as suspicious, further loop (LEEP) cervical excision showed at least 1B1 mesonephric carcinoma of the cervix. Preoperative MRI scan showed a 2.2 cm carcinoma cervix but no metastasis or lymphadenopathy. She underwent radical cervical stumpectomy, upper vaginectomy, bilateral salpingo-oophorectomy, and bilateral pelvic nodes dissection. The histology confirmed the diagnosis, there was no spreading in parametria or lymph nodes, however, vaginal margins were involved. She had further adjuvant chemoradiotherapy. Methods: We conducted a systematic literature review for all English published litrature from january 1960 until December 2019. Results: 67 cases were reported in the literature. The stage was documented only in 58 cases. 60% of those were clinically described as IB. Surgical treatment varied between simple hysterectomy without lymphadenectomy to radical hysterectomy with pelvic lymphadenectomy. In 50% of those who underwent surgery, the vaginal margins were positive. Recurrence was documented in 45% of the patients. Conclusions: The mesonephric cervical tumour appears to have a more aggressive behaviour with higher rates of vaginal extension and recurrence rates despite multiple treatment modalities. There is a clear need for consensus and guidance into the management of this condition.